MODEL PERSEDIAAN TERINTEGRASI PADA SISTEM SUPPLY CHAIN YANG MELIBATKAN PEMASOK, PEMANUFAKTUR DAN PEMBELI - Jauhari, Wakhid Ahmad (Muhammadiyah University Press, 2006)
In this paper we consider a single buyer-single manufacturer- single supplier supply chain problem where there are multiple deliveries for one buyer?s order and the manufacturer produces in a multiple integer of deliveries quantity. We also consider a lot size of raw material procurement which can be split from production batch. From numerical example we found that a value of material conversion factor and delivery frequency influences the total inventory cost . A high value of material conversion factor would make the buyer?s total inventory cost increase and the manufacturer?s total inventory costdecrease. High frequency of delivery would make the buyer?s total inventory cost decrease and the manufacture?s total inventory cost increase.